Elucidating He-H assisted cavity evolution in alpha Cr under multiple ion beam irradiation. (October 2020) - Jiang, Li; Peng, Qing; Xiu, Pengyuan; Yan, Yan; Jiao, Zhijie; Lu, Chenyang; Liu, Tong; Ye, Chao; Shu, Rui; Liao, Yehong; Ren, Qisen; Gao, Fei; et al.
Abstract: Dual and triple ion beam irradiations were performed on alpha-Cr using 5 MeV Fe ++, 2.9 MeV He ++ and/or 270 keV H + to study the synergy of hydrogen and helium on cavity formation. Results indicate that co-implantation of helium with iron enhances cavity nucleation and co-implantation of hydrogen with iron augments cavity growth. Under triple beam irradiation, hydrogen also accelerates cavity nucleation via stabilizing initial embryos. First-principles calculations reveal that the presence of helium increases the maximum number of hydrogen atoms that can be captured by a vacancy from 6 to 9, providing an atomistic explanation to the triple beam synergy. Graphical abstract: Image, graphical abstract